Financeirização e a transformação do espaço urbano: uma análise sobre a região da Vila Leopoldina – São Paulo/SP - César, Fábio Soares (2021)
The capitalist world is presented under a macroeconomic situation driven by the movement, accumulation and generation of capital in various sectors of the economy. The transformation in various sectors of the economy is appreciated, to better take advantage of the possibilities of this financial logic, where the adjustments that have occurred in the real estate sector stand out. In this Thesis, then, the process of financialization of real estate capital is discussed and how this financialization can influence large interventions in the logic of restructuring urban space in the Vila Leopoldina region, located in the city of São Paulo. It is predominantly developed with qualitative and quantitative bibliographic research and documentary research, through secondary sources of various data, such as: documents available on the website of the city of São Paulo, Embraesp and Secovi-SP. It is expected to observe the urban interventions that were carried out, the companies attracted and the Urban Projects implemented and how these may have influenced a potential socio-spatial segregation and gentrification, exodus and the life of the traditional urban population in this region